Malaysian Mesdaq Venture Capital Firms - Signaling Variables Of Firm Value - Harun, Ahmad Najib (2004)
This empirical research investigates eleven factors or variables that provide signaling power of the firm’s performance using data of 37 firms listed on Malaysian MESDAQ market.